2010
DOI: 10.1021/ie900694r
|View full text |Cite
|
Sign up to set email alerts
|

Transient Behavior and Stability in Miniaturized Multiphase Packed Bed Reactors

Abstract: The step response, including various startup procedures, in a three-phase microreactor of 2 mm internal diameter packed with nonporous particles of 100 μm is reported. We demonstrate that the bed behaves reproducibly through many cycles of operating conditions. Interestingly, we find that the different startup procedures have little effect on the steady state that is achieved. In other words, minimal hysteresis was observed, in sharp contrast to larger-scale reactors with larger particles where prewetting has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
0
30
2
Order By: Relevance
“…The hydrodynamics and mass transfer of gas–liquid flow in μPBRs are therefore different from that of TBRs. Márquez et al found the pressure drop and liquid holdup in the range of 30–160 kPa/m and 0.65–0.85 in a μPBR packed with 100 μm glass beads, respectively. The liquid holdup of the μPBR was significantly higher than 0.05–0.2 in large‐scale TBRs .…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamics and mass transfer of gas–liquid flow in μPBRs are therefore different from that of TBRs. Márquez et al found the pressure drop and liquid holdup in the range of 30–160 kPa/m and 0.65–0.85 in a μPBR packed with 100 μm glass beads, respectively. The liquid holdup of the μPBR was significantly higher than 0.05–0.2 in large‐scale TBRs .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the hydrodynamic behavior of microreactors is quite dynamical depending on the previous history. 30 Behavior that is also observed in porous media. 31 An uneven disposition of the solids within a microreactor can have a great effect on the hydrodynamics of micropacked bed reactors.…”
Section: Introductionmentioning
confidence: 82%
“…33 We used before pressure drop measurements over micro-packed bed of particles to understand hold-up, transients and dispersion in these systems. 30,34 However, modelling and visualization in porous media shows that the local pressures over a micropacked bed of pillars vary significantly across the bed. 35 De Loos et al 36 has compared experimental results with different modelling approaches to calculate the pressure drop over a regular arrangement of pillars.…”
Section: Micro-packed Bed Designmentioning
confidence: 99%
“…Similarly, the use of small catalyst particles -i.e. <500 μm of diameter approximately-in miniaturized packed-bed reactors present the following characteristic behavior ( Figure 1): 15  bed is usually saturated with liquid due to strong capillary forces;…”
mentioning
confidence: 99%
“…Adapted with permission from ref. 15. Copyright (2010) American Chemical Society Larachi et al studied the influence of the bed geometry and particle size via wall microscopic visualization and residence time distribution (RTD).…”
mentioning
confidence: 99%